POSITIONAL CATALOGUES OF SATURN’S AND JUPITER’S MOONS - Yizhakevych, O.; Andruk, V.; Pakuliak, I.; Lukianchuk, V.; Shatokhina, S. (Одеські астрономічні публікації, 2014)
In the framework of the UkrVO national project (http://ukr-vo.org/) we have started the processing of photographic observations of Saturn’s (S1-S8) and Jupiter’s (J6-J8) moons. Observations were conducted during 1961–1993 with three astrographs DLFA, DWA, DAZ and Z600 reflector. Plate images were digitized as tif-files with commercial scanners. Image processing was carried out by specific software package in the LINUX-MIDAS-ROMAFOT environment with Tycho2 as reference. The software was developed at the MAO NASU. Obtained positions of objects were compared with theoretically predicted ones in IMCCE (Paris) (www.imcce.fr/sat) online. Rms error of divergence between observed and calculated positions is of 0.20”–0.35”.